Psychoeducation about Adaptive Behaviour among Civil Servants at The National Center for Drug and Food Control (BBPOM) in Palembang - Gusria, Amarisma (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2025)
AKHLAK values are crucial for every ASN to implement as a source of enthusiasm and guidance for workplace behavior. The BPOM is conducting routine assessments to measure the implementation of AKHLAK among employees and to determine its impact on daily work processes. However, the results show that it needs to improve its employees' adaptive behavior relative to other values in AKHLAK. Daily behaviors indicate that some employees still have difficulty adapting to rapidly changing work systems and to constantly changing policies. Employees sometimes feel surprised, afraid, and exhausted, and experience stress from having to adapt continuously. One of the strategies used by BPOM, in collaboration with Psychology at Sriwijaya University, is to provide psychoeducation on adaptability skills. The purpose is to help participants: (1) Identify what challenges, situations, and changes are being experienced and their solutions, (2) Increase awareness and willingness of employees to implement the solution for adaptive behavior in real life, (3) Identify their stress condition and help all employees manage stress effectively with coping stress. The community service method uses psychoeducation and an experiential learning approach with 45 employees. The evaluation used a pre-post test survey and an overall assessment on a 1-5 scale. The results showed an increase in participants' knowledge of adaptive abilities, with scores rising by 20%-43%, and even participants strongly agreed that this agenda could have a significant impact on future work performance.